N-Hexyl-0-glucosyl sphingosine, an inhibitor of glucosyl ceramide, β-glucosidase - John S. Erickson; Norman S. Radin (Journal of Lipid Research, 1973)
A synthetic analog of glucocerebroside, N-hexyl-0-glucosyl sphingosine, was found to inhibit the glucosidase in rat spleen that hydrolyzes glucocerebroside. At a concentration of 1 μm, the analog inhibited the enzyme by 48%. The mode of action appeared to be competitive, probably aided by tight binding of the amine group to a carboxyl group near the enzyme's active site. Increasing or decreasing the chain length of the n-alkyl group attached to the nitrogen atom led to decreased effectiveness. The inhibitory effect was maximal at pH 7.0, but it was still considerable at the enzyme's optimal pH, 5.0. It is suggested that the compound may be useful for inducing an animal model of Gaucher's disease.